Cancer prevalence is increased in females with sleep apnoea: data from the ESADA study. Issue 6 (20th June 2019) - Pataka, Athanasia; Bonsignore, Maria R.; Ryan, Silke; Riha, Renata L.; Pepin, Jean-Louis; Schiza, Sofia; Basoglu, Ozen K.; Sliwinski, Pawel; Ludka, Ondrej; Steiropoulos, Paschalis; Anttalainen, Ulla; McNicholas, Walter T.; et al.
There is growing, but debatable evidence for the potential association between obstructive sleep apnoea (OSA) and cancer [1–10]. Available studies have reached contradictory conclusions due to limited sample sizes, and poor characterisation of OSA phenotypes or type of malignancies (all types [1–4] or site specific [6–8]). Several hypotheses have been formulated proposing why carcinogenesis can occur in the context of OSA, including older age, sleep deprivation [11, 12] and concomitant obesity [13]. Intermittent hypoxia and sleep fragmentation may play a significant role via alterations in angiogenesis, sympathetic outflow, or modulation of immune function and tumour microenvironment [11, 12]. Gender-specific differences in the association between OSA and cancer prevalence have been poorly studied. In a cross-sectional analysis of the European Sleep Apnoea Database (ESADA), cancer prevalence was higher in females with OSA and nocturnal hypoxia, but not in males. Further studies are needed to assess causality of gender, OSA and cancer incidence. http://bit.ly/2YuxyZA